Functional characterization of a geraniol synthase-encoding gene from Camptotheca acuminata and its application in production of geraniol in Escherichia coli. (1st September 2016) - Chen, Fei; Li, Wei; Jiang, Liangzhen; Pu, Xiang; Yang, Yun; Zhang, Guolin; Luo, Yinggang
Abstract: Geraniol synthase (GES) catalyzes the conversion of geranyl diphosphate (GPP) into geraniol, an acyclic monoterpene alcohol that has been widely used in many industries. Here we report the functional characterization of CaGES from Camptotheca acuminata, a camptothecin-producing plant, and its application in production of geraniol in Escherichia coli . The full-length cDNA of CaGES was obtained from overlap extension PCR amplification. The intact and N-terminus-truncated CaGESs were overexpressed in E. coli and purified to homogeneity. Recombinant CaGES showed the conversion activity from GPP to geraniol. To produce geraniol in E. coli using tCaGES, the biosynthetic precursor GPP should be supplied and transferred to the catalytic pocket of tCaGES. Thus, ispA (S80F), a mutant of farnesyl diphosphate (FPP) synthase, was prepared to produce GPP via the head-to-tail condensation of isoprenyl diphosphate (IPP) and dimethylallyl diphosphate (DMAPP). A slight increase of geraniol production was observed in the fermentation broth of the recombinant E . coli harboring t CaGES and ispA (S80F). To enhance the supply of IPP and DMAPP, the encoding genes involved in the whole mevalonic acid biosynthetic pathway were introduced to the E. coli harboring tCaGES and the ispA (S80F) and a significant increase of geraniol yield was observed. The geraniol production was enhanced to 5.85 ± 0.46 mg L −1 when another copy of ispA (S80F) was introduced to the above recombinant strain. The following optimization of medium composition, fermentation time, and addition of metal ions led to the geraniol production of 48.5 ± 0.9 mg L −1 . The present study will be helpful to uncover the biosynthetic enigma of camptothecin and tCaGES will be an alternative to selectively produce geraniol in E. coli with other metabolic engineering approaches.